Organic chemistry for matriculation - Smith, Janice Gorzynski (McGraw-Hill education matriculation series, 2007)
This book is developed for students studying chemistry at matriculation colleges. It is adapted from the 1st edition of Organic Chemistry by Jane Gorzynski Smith, which has been widely used in universities and matriculation colleges as a text or reference. This book's strength lies in its clarity and readability as well as the high quality pictures. In additional, it includes worked examples, as well as questions and problems with answers.